Educational Practices of Nobility in G. F. Kvitka-Osnovyanenko Works - Яковенко, Ганна (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
Based on the analysis of G. F. Kvitka-Osnovyanenko works, the article deals with the contents of nobles’ educational practices: individual studies (tutors, parents) and collective (studies of children’s groups in noble families and boarding-schools). The positive achievements and negative experience of home-schooling noble children are reflected in the first half of the XIX century in the works of G. F. Kvitka-Osnovyanenko. The author drew attention to the foreign influence in education, particularly the French, which did not instill patriotism in the younger generation. Foreign tutors provided a low level of education.